Contributions of an inland carnival to the perspective of post-abolitionist historiographic memory in the 20th and 21st centuries - da Silva , Alberto Bomfim; Farias , Edson (Universidad Pedagógica y Tecnológica de Colombia, 2021)
The objective of this paper is to reflect upon what is conventionally referred to as the post-abolitionist period. It is an analysis derived from studies on the associations of black and mestizo people in the city of Vitória da Conquista (Brazil),amid the political and cultural transitions in the carnivalization process in the second half of the 20th century. The methodology consisted of the interpretation of the iconography, especiallyphotographs of the carnival, and the analysis of the first-hand accounts of the people whose formation of the memory was linked to those groups which held the street carnival, from thepredicates of oral history, articulating postulates from history and other fundamental social disciplines in order to approach the memory. With this investigation, it can be inferred that it is possible to alter the academic use of the post-abolitionist category in the epistemological field of history, substracting its sense of periodization, and inverting the thematic meaning conferred by the inscription of the memory of the struggles forliberty and citizenship of black and mestizo people, making use of a new category: historiographic memory.